The role of type 2 diabetes in neurodegeneration - Verdile, Giuseppe; Fuller, S.; Martins, R. (Academic Press Inc., 2015)
A growing body of evidence links type-2 diabetes (T2D) with dementia and neurodegenerative diseases such as Alzheimer's disease (AD). AD is the most common form of dementia and is characterised neuropathologically by the accumulation of extracellular beta amyloid (Aß) peptide aggregates and intracellular hyper-phosphorylated tau protein, which are thought to drive and/or accelerate inflammatory and oxidative stress processes leading to neurodegeneration. Although the precise mechanism remains unclear, T2D can exacerbate these neurodegenerative processes. Brain atrophy, reduced cerebral glucose metabolism and CNS insulin resistance are features of both AD and T2D. Cell culture and animal studies have indicated that the early accumulation of Aß may play a role in CNS insulin resistance and impaired insulin signalling. From the viewpoint of insulin resistance and impaired insulin signalling in the brain, these are also believed to initiate other aspects of brain injury, including inflammatory and oxidative stress processes. Here we review the clinical and experimental pieces of evidence that link these two chronic diseases of ageing, and discuss underlying mechanisms. The evaluation of treatments for the management of diabetes in preclinical, and clinical studies and trials for AD will also be discussed.